A Tryptophan Metabolite of the Microbiota Improves Neovascularization in Diabetic Limb Ischemia - Ma, Xiurui; Yang, Jinjing; Yang, Guanrui; Li, Lei; Hao, Xiaojun; Wang, Guoqin; An, Jian; Wang, Fei (Frontiers in Cardiovascular Medicine, 2022)
Diabetes mellitus (DM) is accompanied by a series of macrovascular and microvascular injuries. Critical limb ischemia is the most severe manifestation of peripheral artery disease (PAD) caused by DM and is almost incurable. Therapeutic modulation of angiogenesis holds promise for the prevention of limb ischemia in diabetic patients with PAD. However, no small-molecule drugs are capable of promoting diabetic angiogenesis. An endogenous tryptophan metabolite, indole-3-aldehyde (3-IAld), has been found to have proangiogenic activity in endothelial cells. Nevertheless, the role of 3-IAld in diabetic angiogenesis remains unknown. Here, we found that 3-IAld ameliorated high glucose-induced mitochondrial dysfunction, decreasing oxidative stress and apoptosis and thus improving neovascularization.